I-A(g7) is subject to post-translational chaperoning by CLIP - Rinderknecht, Cornelia H. (Oxford University Press, 2010)
Several MHC class II alleles linked with autoimmune diseases form unusually low-stability complexes with class II-associated invariant chain peptides (CLIP), leading us to hypothesize that this is an important feature contributing to autoimmune pathogenesis. We recently demonstrated a novel post-endoplasmic reticulum (ER) chaperoning role of the CLIP peptides for the murine class II allele I-E(d). In the current study, we tested the generality of this CLIP chaperone function using a series of invariant chain (Ii) mutants designed to have varying CLIP affinity for I-A(g7). In cells expressing these Ii CLIP mutants, I-A(g7) abundance, turnover and antigen presentation are all subject to regulation by CLIP affinity, similar to I-E(d). However, I-A(g7) undergoes much greater quantitative changes than observed for I-E(d). In addition, we find that Ii with a CLIP region optimized for I-A(g7) binding may be preferentially assembled with I-A(g7) even in the presence of higher levels of wild-type Ii. This finding indicates that, although other regions of Ii interact with class II, CLIP binding to the groove is likely to be a dominant event in assembly of nascent class II molecules with Ii in the ER.